A Flexible Triboelectric Nanogenerator Based on Cellulose‐Reinforced MXene Composite Film. Issue 7 (1st February 2022) - Yang, Wei; Chen, Huamin; Wu, Mingqiang; Sun, Zhaoyang; Gao, Min; Li, Wenjie; Li, Chenyu; Yu, Hualiang; Zhang, Cheng; Xu, Yun; Wang, Jun
Abstract: A flexible triboelectric nanogenerator (TENG) is an indispensable part in future flexible self‐powered system. However, it is still a great challenge to establish a balance among the robust mechanical property, strong triboelectrification effect, and high conductivity of electrode materials. A flexible and enhanced‐performance TENG based on cellulose nanofibrils (CNFs)/transition metal carbides and nitrides (MXene) composite films is developed here for harvesting human movement energy. By introducing CNFs, the mechanical strength, flexibility of the composite film, and sensitive to the temperature change and strain are improved. The effect of CNFs concentration, working force, and frequency on the output performance of TENG is also demonstrated. At the optimized CNFs/MXene ratio of 2/5, the transferred charges and output voltage reach the maximum value of 7.4 nC and 24.9 V, respectively. The maximum instantaneous output power density of the as‐prepared TENG is 1.2 mW m −2 . Moreover, a self‐powered flexible display system is demonstrated by integrating the TENG with a flexible alternating current electroluminescence. The flexible TENG based on cellulose nanofibrils‐reinforced MXene composite film is promising as a flexible energy source for self‐powered system. Abstract : A flexible cellulose nanofibrils (CNFs)/transition metal carbides and nitrides composite electrode sensitive to temperature change and strain is developed first. By introducing CNFs, the mechanical strength and flexibility of the composite electrode are increased. Moreover, a self‐powered flexible display system is demonstrated by integrating the triboelectric nanogenerator (TENG) with a flexible alternating current electroluminescence.